The effectiveness of home self-foot massage using a massage wood device on foot sensation and balance performance in patients with diabetes mellitus - Chanumklang, Kanyarat; Peungsuwan, Punnee; Donrapunha, Wanida; Chatchawan, Uraiwan; Sriboonreung, Thanyaluck (Archives of Allied Health Sciences, 2019)
The purpose of this study was to investigate the effectiveness of self-foot massage using a massage wood device on foot sensation and balance performance and to compare with the self-foot massage using thumbs in patients with type 2 diabetes mellitus. Forty patients with type 2 diabetic were randomly allocated to either the experimental group (EG) or control group (CG), n=20/group. The CG (aged 66.6 ± 4.2 years) subjects received the home self-foot Thai massage using thumbs and the EG (aged 66.0 ± 4.0years) individuals received the home self-foot massage using a massage wooden device. Each subject was trained own massage and they had to perform at their home, 30 minutes of both feet (15 minutes per a side), 7 times/week for 4 weeks. Semmes-Weinstein monofilament test (SWMT), Time up and go test (TUG) and one leg standing test (OLS) were measured at before, and after 2-week and 4-week interventions. Repeated-measures analysis of variance was used for comparing within group. The EG showed statistically significant improvements of the SWMT, TUG and OLS (opened and closed eyes) after 2-week and 4-week massage. In the CG showed statistically significant improvement of the SWMT and TUG when compared between the baselines and after 4-week massage, and comparing after 2-week and 4-week massage. In comparing between groups, analysis of covariance was tested. All of the outcomes were better improvements in the experiment group compare to after the 2-week and 4-week (p<0.001) interventions, except the right leg OLS with opened eye of the after 2-week. Conclusion, this study show that a self-foot massage wooden device is beneficial on foot sensation and balance performance for patients with type-2 diabetes.